The disconnect between research and current coaching practices - Judge, L. W.; Craig, B. (Strength and Conditioning Journal, 2014)
Today's coaches do not use many of the current research recommendations for pre- and post-stretching, even though many of them have completed certification programs designed to help them develop evidence-based practices. This article will briefly review the current recommendations for stretching and present data that show a lack of compliance with these recommendations. The purpose of the discussion will be to identify the extent to which certification might affect coaching practices.